Civil Law and Common Law: Two Different Paths Leading to the Same Goal - Pejovic, Caslav (Victoria University of Wellington Law Review, 2001)
"There are many ways to skin a cat". While there are many legal issues which are dealt with in the same way by the civil law and Common Law systems, there remain also significant differences between these two legal systems related to legal structure, classification, fundamental concepts and terminology. This paper does not deal with theoretical examination of differences between the common law and the civil law, but focuses rather on various distinctive features of civil law and common law, with several illustrations of resulting differences in both substantive law and procedural law. These differences are not examined in detail as they should serve only as illustration of those differences. The paper does not enter into polemic as to which legal system is better and what are the advantages of common law or of civil law. The purpose of this short study is simply to highlight some of the main conceptual differences between common law and civil law systems, and to explore the possibilities of reconciling of some of those differences.